2016
DOI: 10.3892/or.2016.4605
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-5, a ubiquitin ligase scaffold protein, is significantly underexpressed in endometrial adenocarcinomas and is a target of miR-182

Abstract: Abstract. Altered expression of cullin-5 (CUL5), a member of the cullin-RING E3 ubiquitin ligase family, has been implicated in a number of types of cancers including breast, cervical and hepatocellular cancers. In the present study, we found that CUL5 expression was significantly decreased in both endometrioid and serous endometrial adenocarcinomas with the more aggressive serous type displaying a higher reduction (-4.3-fold) than the less aggressive endometrioid type (-2.9-fold). Overexpression of CUL5 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(38 reference statements)
1
13
1
Order By: Relevance
“…High antigen KI-67 and CUL5 expression levels in tissues are associated with cancers [44,[52][53][54][55][56]. We observed increased serum concentrations of these proteins in patients with CKD in this study.…”
Section: Discussionsupporting
confidence: 60%
“…High antigen KI-67 and CUL5 expression levels in tissues are associated with cancers [44,[52][53][54][55][56]. We observed increased serum concentrations of these proteins in patients with CKD in this study.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we revealed 56 dysregulated miRNAs through which endometrial cancer tissues can be distinguished from benign endometrium. Some of these miRNAs have been reported in endometrial cancer before, such as miR-200a (14), miR-182 (37), and miR-183 (38). These data suggest that miRNAs play important roles in tumorigenesis.…”
Section: Discussionmentioning
confidence: 67%
“…miRNAs express aberrantly in cancers and have a profound effect on many processes that are usually disrupted during malignant transformation, such as cell proliferation, apoptosis, stress responses, maintenance of stem cell potency, and metabolism (36). Recent advances have suggested that dysregulation of miRNAs is a common event in endometrial cancer (37). In this study, we revealed 56 dysregulated miRNAs through which endometrial cancer tissues can be distinguished from benign endometrium.…”
Section: Discussionmentioning
confidence: 80%
“…CUL5 was significantly downregulated in serous endometrial adenocarcinoma with a poor prognosis, compared with its level in endometrial carcinoma with a good prognosis (58). The action of CUL5 involves non-coding RNAs (ncRNAs), which are RNAs that do not include genetic information for protein synthesis.…”
Section: Diagnosis Of Endometrial Cancer and Epigenetic Abnormalitiesmentioning
confidence: 99%
“…Two highly-conserved miR-182-binding regions are present in the 3'-UTR of CUL5, and CUL5 targets miR-182 in endometrial cancer. CUL5 downregulation causes miR-182 upregulation and progression of endometrial cancer (58). Zhou et al demonstrated that miR-30c overexpression inhibited metastasis-associated gene-1 (MTA1) (59).…”
Section: Diagnosis Of Endometrial Cancer and Epigenetic Abnormalitiesmentioning
confidence: 99%